The treatment of hypertensive disorders in pregnancy. Issue 1 (January 2023) - Routledge, Elizabeth; Marsden, Sarah
Abstract: Hypertensive disorders are among the most common complications of pregnancy, affecting 8–10% of all pregnancies. They include gestational hypertension, pre-eclampsia and eclampsia, as well as pregnant patients with pre-existing chronic hypertension. Over the last 70 years, there has been marked decline in maternal mortality associated with hypertension. The development of pre-eclampsia and eclampsia is mediated by the placenta, and results in a widespread inflammatory response with consequent endothelial dysfunction and thus both multisystem maternal organ dysfunction and uteroplacental failure. The identification of patients at risk and the early diagnosis and therefore treatment of patients who develop pre-eclampsia can be life-saving to both mother and fetus. A patient with a hypertensive disorder of pregnancy presents specific considerations for the obstetric anaesthetist around timing and mechanism of delivery, including the implications for delivery of both regional and general anaesthesia. The most unwell patients may need to be managed in a critical care environment. These considerations all require a strong multidisciplinary approach involving anaesthetics, critical care, obstetrics, and paediatrics.